ANALYSIS OF BUSINESS OPPORTUNITIES FOR DUCK BONE WASTE MEAL AS AN ALTERNATIVE FEED ADDITIVE FOR LAYER CHICKENS: Analisis Peluang Usaha Limbah Tepung Tulang Itik sebagai Aditif Pakan Alternatif untuk Ayam Petelur - Haryono, Iranita; Padapi, Astrini; Salim, Agus; Muh. Reksiyandi; Irwangsyah, Andi (Unit Penelitian dan Pengabdian Masyarakat Politeknik Pembangunan Pertanian Gowa, 2025)
Nasu palekko, made from duck meat, is one of the typical dishes of Sidenreng Rappang Regency.The amount of duck bone waste produced has increased due to the rising demand for this product.The business potential of duck bone meal; the livestock feed production process, which includes production inputs, receipts, and revenue; and the added value generated from processing duck bone meal.This study was conducted in Sidenreng Rappang Regency from June to November 2022.Qualitative and quantitative descriptive analysis of the production process and its inputs, income and profit analysis, and the Hayami method for calculating added value were used in this research.According to the research results, the duck bone flour industry has a lot of potential.The production capacity of duck bone meal per day is 4,400 kilograms with a margin of Rp15,168,000.Meanwhile, the added value per production according to the Hayami technique is Rp5,603,000.